Postmortem assay of digoxin by radioimmunoassay. - Holt, D W (1975)
Analysis of postmortem blood samples from patients previously on maintenance digoxin therapy suggests that the results are of value in assessing the degree of digitalization at the time of death. Control cases gave results within the normal therapeutic range wheras of six cases in which digoxin was suspected of being implicated in the death five had 'serum' digoxin levels above the therapeutic range. Differences in digoxin concentration were noted in blood collected from three sites in the body, and it is suggested that postmortem blood should be collected from the leg veins if assessment of antermortem digitalization is to be made.